Usuń nawiasy i zredukuj wyrazy podobne
1.(2x+1)(x-3)
2.(x-3)(x+5)
3.(-2x+3)(x+3)
4.(3x-1)(x+5)
5.4x+3)(2x-4)
6.(-3x-4)(x+2)
7.(x-5)(-x+4)
8.(3x-4)(-x-5)
9.(-x+5)(x+4)+2
10.(3x+5)(x-4)-x
11.(-x-5)(x+8)-3r
12.3x+(x-5)(x-6)
13.(x+2x+(3x-8)(3x-8)-(x-2)
14.x-4x+(2x+5)(-x-1)
15.5x+(-2x+4)(x-5)
16.x+(4x-1)(x-1)
17.4x+(x-7)(x+4)
18.(2x-7)(x+6)+x
19.(x-8)(x-2)-x
20(x-10)(x+12)















2

Odpowiedzi

2009-12-06T17:58:58+01:00
1.(2x+1)(x-3)= 2x² - 6x + 1x - 3 = 2x² - 5x-3
2.(x-3)(x+5) = x² + 5x -3x-15 = x² + 2x - 15
3.(-2x+3)(x+3) = -2x² - 6x + 3x + 9 = -2x² -3x +9
4.(3x-1)(x+5) = 3x² + 15x -1x -5 = 3x² + 14x -5
5.(4x+3)(2x-4) = 8x² - 16x + 6x -12 = 8x² -10x -12
6.(-3x-4)(x+2) = -3x² - 6x - 4x -8 = -3x² -10x -8
7.(x-5)(-x+4) = -x² + 4x + 5x -20 = -x² + 9x -20
8.(3x-4)(-x-5) = -3x² - 15x +4x +20 = -3x² -11x +20
9.(-x+5)(x+4)+2 = -x² - 4x + 5x + 20 +2 = -x² + x + 22
10.(3x+5)(x-4)-x = 3x² - 12x + 5x - 20 -x = 3x² -8x - 20
11.(-x-5)(x+8)-3r = -x² -8x -5x -40 - 3r = -x² - 13x - 40 -3r
12.3x+(x-5)(x-6) = 3x + x² - 6x - 5x +30 = -8x + x² + 30
2009-12-06T18:10:38+01:00
1.(2x+1)(x-3)=2x²-6x+x-3=2x²-5x-3
2.(x-3)(x+5)=x²+5x-3x-15=x²+2x-15
3.(-2x+3)(x+3)=-2x²-6x+3x+9=-2x²-3x+9
4.(3x-1)(x+5)=3x²+15x-x-5=3x²+14x-5
5.4x+3)(2x-4)=8x²-14x+6x-12=8x²-8x-12
6.(-3x-4)(x+2)=-3x²-6x-4x-8=-3x²-10x-8
7.(x-5)(-x+4)=-x²+4x+5x-20=x²+9x-20
8.(3x-4)(-x-5)=-3x²-15x+4x+20=-3x²-11x+20
9.(-x+5)(x+4)+2=-x²-4x+5x+20+2=-x²+x+22
10.(3x+5)(x-4)-x=3x²-12x+5x-20-x=3x²-8x-20
11.(-x-5)(x+8)-3r=-x²-8x-5x-40-3r=-x²-13x-3r-40
12.3x+(x-5)(x-6)=3x+x²-6x-5x+30=x²8x+30
13.(x+2x+(3x-8)(3x-8)-(x-2)=x+2x+9x²-64-x+2=9x²+2x-62
14.x-4x+(2x+5)(-x-1)=x-4x-2x²-2x-5x-5=-2x²-10x-5
15.5x+(-2x+4)(x-5)=5x-2x²+10x+4x-20=-2x²+19x-20
16.x+(4x-1)(x-1)=x+4x²-4x-x+1=4x²-4x+1
17.4x+(x-7)(x+4)=4x+x²+4x-7x-28=x²+1-28
18.(2x-7)(x+6)+x=2x²+12x-7x-42+x=2x²+6-42
19.(x-8)(x-2)-x=x²-2x-8x+16=x²-10+16
20(x-10)(x+12)=x²+12x-10x-120=x²+2x-120